1981
DOI: 10.1029/ja086ia13p11439
|View full text |Cite
|
Sign up to set email alerts
|

Solar cycle induced modulation of the 55‐MeV proton fluxes at low altitudes

Abstract: Experiments flown on U.S. Air Force Satellites from 1961 until 1976 have measured the 55-MeV proton flux at low altitudes, between 275 km and 600 km. The analysis of these data shows that in spite of all the uncertainties involved, the agreement obtained between the theoretical calculations and the data is quite good. We conclude that the major determining factors of the 55-MeV proton fluxes in the inner zone are a nearly constant source coupled with a solar cycle varying atmospheric ionization loss process. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…The relative variation is 2.9% for >36‐MeV protons and 2.7% for >140‐MeV protons, even though the altitude difference is only 21 km. This detailed feature suggests that trapped inner belt protons have a strong altitude gradient, confirming early results (e.g., Parsignault et al, 1981). This spatial gradient also suggests that there would be an east‐west asymmetry if measured by a unidirectional detector as the eastward traveling fluxes, whose guiding centers are at higher altitudes, are expected to be greater than the westward traveling fluxes, whose guiding centers are at lower altitudes because of the finite protons gyroradii (Heckman & Nakano, 1963; Lenchek & Singer, 1962).…”
Section: Observations and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The relative variation is 2.9% for >36‐MeV protons and 2.7% for >140‐MeV protons, even though the altitude difference is only 21 km. This detailed feature suggests that trapped inner belt protons have a strong altitude gradient, confirming early results (e.g., Parsignault et al, 1981). This spatial gradient also suggests that there would be an east‐west asymmetry if measured by a unidirectional detector as the eastward traveling fluxes, whose guiding centers are at higher altitudes, are expected to be greater than the westward traveling fluxes, whose guiding centers are at lower altitudes because of the finite protons gyroradii (Heckman & Nakano, 1963; Lenchek & Singer, 1962).…”
Section: Observations and Discussionsupporting
confidence: 90%
“…We have also demonstrated that the inner belt proton intensity and solar cycle variation measured at LEO also depends sensitively on altitude. Such behavior of inner belt protons was predicted by theory decades ago (e.g., Blanchard & Hess, 1964) simply based on the source and loss mechanisms and also demonstrated with various satellites measurements (e.g., Huston & Pfitzer, 1998; Parsignault et al, 1981). Here, we have revisited this behavior and analyzed it in more quantitative detail, including comprehensive modeling of protons mirroring near the magnetic equator with direct comparison to measurements.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Many works have reported that solar cycle has long‐term influence on the high‐energy protons in the inner radiation belt (Huston et al., 1998; Malakhov et al., 2016; Parsignault et al., 1981; Qin et al., 2014). However these works are mainly focusing on low‐altitude region ( L < 1.5) and present the anticorrelated relationships between variations of high‐energy protons and solar F10.7 flux.…”
Section: Analysis Resultsmentioning
confidence: 99%
“…Parsignault et al. (1981) found that the 55‐MeV proton fluxes at low altitudes (275–600 km) are affected by atmospheric ionization process which is caused by strong solar cycle effect. Dragt (1971) predicted variation in the trapped radiation belt proton fluxes varying with the solar cycle on the assumption of a neutron decay source.…”
Section: Introductionmentioning
confidence: 99%